Adult age-differences in subjective impression of emotional faces are reflected in emotion-related attention and memory tasks - Joakim eSvard; Joakim eSvard; Håkan eFischer; Håkan eFischer; Daniel eLundqvist (Frontiers in Psychology, 2014)
Although younger and older adults appear to attend to and remember emotional faces differently, less is known about age-related differences in the subjective emotional impression (arousal, potency, and valence) of emotional faces and how these differences, in turn, are reflected in age differences in various emotional tasks. In the current study, we used the same facial emotional stimuli (angry and happy faces) in four tasks: emotional rating, attention, categorical perception, and visual short-term memory (VSTM). The aim of this study was to investigate effects of age on the subjective emotional impression of angry and happy faces and to examine whether any age differences were mirrored in measures of emotional behavior (attention, categorical perception, and memory).In addition, regression analyses were used to further study impression-behavior associations. Forty younger adults (range 20-30 years) and thirty-nine older adults (range 65-75 years) participated in the experiment. The emotional rating task showed that older adults perceived less arousal, potency, and valence than younger adults and that the difference was more pronounced for angry than happy faces. Similarly, the results of the attention and memory tasks demonstrated interaction effects between emotion and age, and age differences on these measures were larger for angry than for happy faces. Regression analyses confirmed that in both age groups, higher potency ratings predicted both visual search and visual short-term memory efficiency. Future studies should consider the possibility that age differences in the subjective emotional impression of facial emotional stimuli may explain age differences in attention to and memory of such stimuli.